PENERAPAN MODEL INKUIRI TERBIMBING PADA KONSEP USAHA DAN ENERGI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF, AKTIVITAS, DAN HASIL BELAJAR SISWA KELAS X MIPA.2 SMAN 10 KOTA BENGKULU - Junisa Anggun Lestari; Afrizal Mayub; Nyoman Rohadi (UNIB Press, 2017)
This research is a classroom action research (CAR) conducted in four cycles that aims to improve the ability of creative thinking, activities, and students’ learning outcomes on work and energy concepts. The subjectwas33 students of grade X. Data obtained from the test and observation sheets were analysed in the descriptive method. CAR was conducted in four stages, that, planning, action, observation, and reflection. Instruments used in the research were the creative thinking testand the achievementtest, observation sheet of teacher and activities and student. The results showed that the result of the creative thinking test obtained the average score of 64.38 in cycle I, increased to 71,36 in cycle II, increased to 74,45 in cycle III, and increased to 76.34 in cycle IV. Student learning activity on cycle I was with average score 22, increased to 31 in cycle II, increased to 36 in cycle III, and increase to 37 in cycle IV. Students' learning outcomes in the first cycle becaming of 74.19%, increased in cycle II of 83.87%, increased in cycle III of 90.32%, and increased in the cycle IV of 100% (thorough). Based on the results of research that the implementation of guided inquiry on work and energy concepts can improve the creative thinking, students’ activities, and learning outcomes. Keywords: guided inquiry, creative thinking skill, learning activities, learning outcomes.